BITUMENS AND BITUMEN COMPOSITIONS BASED ON OIL-CONTAINING WASTES (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article analyzes methods for recycling oil sludge, indicating the advantages and disadvantages of these methods, and also proposes a method of electric combustion technology with environmentally friendly combustion of fuel briquettes.